Environmental, Social, and Governance (ESG) Practices in Sustainable Business Models: Evidence from Nepal - Regmi, Rachana; Khanal, Biduta; Bista, Pooja (Nepalese Journal of Management and Technology, 2025)
This study investigates the adoption, effectiveness, and challenges of Environmental, Social, and Governance (ESG) practices among Nepalese businesses and their role in fostering sustainable business models. Employing a quantitative design, data were collected from 210 respondents across banking, manufacturing, tourism, hydropower, and retail sectors within the Kathmandu Valley. Analyses using descriptive and inferential techniques reveal moderate implementation of environmental and social initiatives, driven primarily by stakeholder expectations and rising consumer awareness. Governance practices, however, remain underdeveloped due to weak regulatory enforcement, limited transparency, and inadequate institutional oversight. Regression results highlight organizational culture and leadership commitment as the strongest drivers of ESG integration, with financial resources and regulatory support also contributing meaningfully. The findings emphasize that without robust governance frameworks, ESG efforts risk remaining symbolic rather than transformative. By providing empirical insights from a developing economy, this study informs policymakers and business leaders on strategies to strengthen ESG adoption and advance sustainable transitions in emerging markets like Nepal.